2016
DOI: 10.3390/nu8010059
|View full text |Cite
|
Sign up to set email alerts
|

Korean Pine Nut Oil Attenuated Hepatic Triacylglycerol Accumulation in High-Fat Diet-Induced Obese Mice

Abstract: Korean pine nut oil (PNO) has been reported to influence weight gain and lipid metabolism. We examined whether PNO replacement in a high-fat diet (HFD) can ameliorate HFD-induced hepatic steatosis. Five-week-old male C57BL mice were fed control diets containing 10% of the energy from fat from PNO or soybean oil (SBO) (PC, SC) or HFDs with 45% of the energy from fat, with 10% from PNO or SBO and 35% from lard (PHFD, SHFD), for 12 weeks. Body weight gain and amount of white adipose tissue were lower in PHFD (10%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 45 publications
(51 reference statements)
0
33
0
Order By: Relevance
“…However, it is important to emphasize that, according to the oil used, possible rancidity and oxidation of the compounds should be considered. To circumvent this adversity, researchers added 0.2 µg of t-butylhydroquinone/g of oil to mice diets and performed daily feed exchanges [30].…”
Section: Dietmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to emphasize that, according to the oil used, possible rancidity and oxidation of the compounds should be considered. To circumvent this adversity, researchers added 0.2 µg of t-butylhydroquinone/g of oil to mice diets and performed daily feed exchanges [30].…”
Section: Dietmentioning
confidence: 99%
“…Obese Treatment [29] 13% kcal from fat 49% kcal fat content Not applicable 49% kcal fat content [30] 10% kcal from fat 35% kcal fat content 10% kcal from fat 35% kcal fat content [31] 10% kcal from fat 50% kcal fat content 10% kcal from fat 50% kcal fat content [32] 10% kcal from fat 50% kcal fat content Not applicable 50% kcal fat content [33] − 46% kcal fat content Not applicable 46% kcal fat content [34] 12% It is noteworthy that the experiments that choose this design should adjust the percentage of kcal from fat in the control and treatment obese groups and even, depending on the objective of the work, consider balancing the amounts of saturated, monounsaturated and polyunsaturated fatty acids, for example, when comparing the ratio between omega-6 and omega-3. The authors highlighted the importance of matching the fat content (as shown in Table 5).…”
Section: Lean Control Obese Control Lean Treatmentmentioning
confidence: 99%
“…Different types of oils have different amounts and compositions of fatty acids, and both are important in regulating hepatic lipid metabolism 33 . The saturated fatty acid could promote the progression of lipids accumulation in the liver, while the unsaturated fatty acids are essential for lipid metabolism 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Different types of oils have different amounts and compositions of fatty acids, and both are important in regulating hepatic lipid metabolism 33 . The saturated fatty acid could promote the progression of lipids accumulation in the liver, while the unsaturated fatty acids are essential for lipid metabolism 33 . Plenty of studies have reported that EMO rich in unsaturated fatty acid, especially linoleic acid, oleic acid and linolenic acid 4,20,25 , and our data showed that unsaturated fatty acid in EMO was reached to 91.28 .…”
Section: Discussionmentioning
confidence: 99%
“…PLA is a unique fatty acid found in pine nut oil, and Korean pine nut oil was reported to decrease body weight gain (Ferramosca, Savy, Einerhand, & Zara, ) and attenuate body fat accumulation (Park, Lim, Shin, & Han, ) in vivo . It also promoted thermogenic response of BAT by activating p38 MAPK (Le et al, ) and induced hepatic fatty acid oxidation in high‐fat diet‐induced obese mice (Park et al, ). In C2C12 myocytes, PLA increased PPARα and PPARδ activity, and upregulated Ucp3 and Pgc1a expression (Le et al, ).…”
Section: Discussionmentioning
confidence: 99%